Beyond the crisis: transitioning to a better world?. Issue 2 (4th May 2021) - Ang, Ien
ABSTRACT: The COVID-19 crisis of 2020 is not just a short-term public health emergency. Instead, it has laid bare a broader and deeper organic crisis, produced by the intrinsic tensions and contradictions of the hegemonic neoliberal capitalist order. I discuss this organic crisis in terms of its active amplification of human divisiveness at various levels – class, racial, national, cultural – which impedes the generation of solidarity and cooperation in the name of a 'common humanity', required if humans are to live in harmony among each other and with the planet. By reflecting on a diverse range of barriers to such a desirable future, from the erosive role of human passions to the escalating new cold war between China and the West and the fundamental divisions exposed by the existential challenge of climate change, I argue that to have a chance of a liveable and equitable common future, we need to maintain a critical cosmopolitan horizon against the grain of self-interested closures and exclusions which underpin the organic crisis.